2014
DOI: 10.1016/j.colsurfb.2014.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Proteins, platelets, and blood coagulation at biomaterial interfaces

Abstract: Blood coagulation and platelet adhesion remain major impediments to the use of biomaterials in implantable medical devices. There is still significant controversy and question in the field regarding the role that surfaces play in this process. This manuscript addresses this topic area and reports on state of the art in the field. Particular emphasis is placed on the subject of surface engineering and surface measurements that allow for control and observation of surface-mediated biological responses in blood a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
301
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(305 citation statements)
references
References 219 publications
(255 reference statements)
4
301
0
Order By: Relevance
“…Creating a submicron-textured surface can dramatically reduce the accessible contact area for platelets or bacteria to interact with the surface, thereby minimizing the opportunities for bacteria and platelet adsorption. 102104 Polymers that combine multiple functional groups on one surface have also been tested, such as combining synthetic heparin-mimetic polymer or hydrophilic polymer brushes (e.g., PEG) with antibacterial quaternary compounds (QAC) or Ag nanoparticles. 105107 …”
Section: Creating Dual-functionality Hemocompatible Surfacesmentioning
confidence: 99%
“…Creating a submicron-textured surface can dramatically reduce the accessible contact area for platelets or bacteria to interact with the surface, thereby minimizing the opportunities for bacteria and platelet adsorption. 102104 Polymers that combine multiple functional groups on one surface have also been tested, such as combining synthetic heparin-mimetic polymer or hydrophilic polymer brushes (e.g., PEG) with antibacterial quaternary compounds (QAC) or Ag nanoparticles. 105107 …”
Section: Creating Dual-functionality Hemocompatible Surfacesmentioning
confidence: 99%
“…The chemistry of the implant surface as well as its physicochemical properties such as wettability or surface energy, and surface topography were found to be important factors that dictate protein adsorption, and platelet adhesion and activation [9][10][11][12] . Regulation of platelet adhesion onto the surface of a blood contacting implant is a key aspect in the field of biomedicine and tissue engineering [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…This could be detrimental for the thrombogenicity of the nanostructured surfaces. However, some authors [3] suggested that not only the total amount of adsorbed FBG, but also its conformation can influence the thrombogenicity of a surface by exposing platelet-binding sites. All treated surfaces displayed a higher adsorbed albumin to fibrinogen ratio than the untreated samples.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the surface topography also influence protein adsorption. There seems to be no general trend in the effect of textured surfaces on the amount of adsorbed protein [3]. Competitive adsorption tests revealed that, despite the limiting effect exerted by FBG on the adsorption of HSA, treated surfaces have a higher adsorbed HSA/FBG ratio, indicating lower thrombogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation